Origin of the change in giant magnetoresistance effects of Fe/V multilayer by hydrogen absorption - Satoshi Akamaru; Kyosuke Miyake (APL Materials)
This study investigated the giant magnetoresistance (GMR) effect of a Fe/V(001) multilayer under different hydrogen concentrations in a hydrogen–nitrogen gas mixture to elucidate the effect of hydrogen absorption in the V layer on the exchange interactions between each Fe layer. The resistance against hydrogen concentration in the gas mixture revealed a phase boundary that was dependent on the V thickness in Fe/V, between hydrogen dissolved in the V metal and V hydride phases. The magnetoresistance in Fe/V with a V thickness of 1.7–2.0 nm demonstrated a GMR effect, which was reduced under low hydrogen concentration in the gas mixture, corresponding to the hydrogen dissolved phase in the V layer. However, Fe/V samples with V thicknesses within the range of 2.2–2.7 nm exhibited the GMR effect during the formation of the V hydride phase, although these samples did not display any GMR behavior under nitrogen gas. These behaviors were reversible to hydrogen concentration in the gas mixture. The dependence of the exchange coupling coefficient on the V layer thickness was estimated from the GMR behavior, revealing that the exchange coupling coefficient was governed by the change in the crystalline phase from the V metal to the hydride and not by the thickness of the V layer. In the V hydride phase, the GMR effect was gradually reduced following hydrogen absorption, suggesting that the induced structural disorder and/or stress in the V layer due to excess hydrogen absorption inhibited the exchange interactions between each Fe layer.